Hepatoprotective Effect of Steroidal Glycosides From Dioscorea villosa on Hydrogen Peroxide-Induced Hepatotoxicity in HepG2 Cells - Siddiqui, Maqsood A.; Ali, Zulfiqar; Chittiboyina, Amar G.; Khan, Ikhlas A. (Frontiers in Pharmacology, 2018)
Dioscorea villosa, commonly known as 'Wild Yam' and native to North America, is well documented for its pharmacological properties due to the presence of steroidal glycosides. However, the hepatoprotective potential of these compounds has not been studied so far. The present investigation was aimed to study the hepatoprotective effect of the steroidal glycosides from D. villosa against H2O2, a known hepatotoxin, in human liver cell line (HepG2). Cytotoxicity assessment was carried out in cells exposed to various concentrations (10-50 M) of compounds for 24 h using MTT assay and morphological changes. All tested compounds were known and among them, spirostans (zingiberensis saponin I, dioscin, deltonin and progenin III) were found to be cytotoxic whereas, furostans (huangjiangsu A, pseudoprotodioscin, methyl protobioside, protodioscin and protodeltonin) were non-cytotoxic. Further, HepG2 cells were pretreated with biologically safe concentrations (10, 30 and 50 M) of non-cytotoxic compounds and then cytotoxic (0.25 mM) concentration of H2O2. After 24 h, cell viability was assessed by MTT and NRU assays, while morphological changes were observed under the microscope. The results showed that treatment of HepG2 cells with compounds prior to H2O2 exposure effectively increased cell viability in a concentration-dependent manner. Furthermore, huangjiangsu A, pseudoprotodioscin, methyl protobioside, protodioscin and protodeltonin at 50 M increased GSH level and decreased intracellular ROS generation against H2O2 induced damages. The results from this study revealed that compounds isolated from D. villosa have hepatoprotective potential against H2O2 induced cytotoxicity and ROS generation and could be promising as potential therapeutic agents for liver diseases.